Steady agronomic and genetic interventions are essential for sustaining productivity in intensive rice cropping - Ladha, Jagdish K.; Radanielson, Ando M.; Rutkoski, Jessica Elaine; Buresh, Roland J.; Dobermann, Achim; Angeles, Olivyn; Pabuayon, Irish Lorraine B.; Santos-Medellín, Christian; Fritsche-Neto, Roberto; Chivenge, Pauline; Kohli, Ajay (National Academy of Sciences, 2021)
SignificanceSteady agronomic and genetic interventions helped sustain high annual rice production in an intensive irrigated monoculture system under a changing climate. However, the system did not achieve the increases in yield required to keep pace with the growing global demand for rice because annual yield potential was stagnant, and apparent biotic constraints limited yield in the wet season.